Arctic Air Cooler - Soukup, Josef; Přibil, Petr; Skočilasová, Blanka (Manufacturing Technology Journal, 2015)
The article deals with the design of a process recirculation air cooler for cooling natural gas when the latter is processed. The cooler is intended for extreme climatic conditions, and due to this reason, it is necessary when designing and fabricating the cooler to comply with the specific requirements for both the calculation and materials to be used on constructing it. In the winter period when the ambient temperature drops even below the solidification point of the medium the cooler works with reduced rpm of the fan, and when necessary, even in the recirculation mode, partial or full (depending on the ambient temperature). In this case, the inlet and outlet louvers are closed, and the recirculation louvers are opened. This system allows, using the control of the temperature of the inlet cooling air, to maintain the temperature of the cooled medium at the desired level.
Keywords: air cooler; recirculation; tube bundle; thermal design quation